2015
DOI: 10.1136/bmjdrc-2015-000094
|View full text |Cite
|
Sign up to set email alerts
|

An observational study of patient characteristics and mortality following hypoglycemia in the community

Abstract: ObjectivesCharacterize patients with diabetes with severe hypoglycemia requiring emergency services intervention at home and investigate 12-month mortality.Research design and methodsEmergency services call-outs for hypoglycemia were recorded between 2005 and 2013 in an area covering 34 000 patients with diabetes. Patient characteristics were documented together with capillary blood glucose (CBG), glycated hemoglobin (HbA1c), and treatment for hypoglycemia; 12-month mortality and variables influencing survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
61
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 28 publications
11
61
1
Order By: Relevance
“…Of particular concern is the link between recurrent hypoglycemic events and cardiovascular risk, cognitive impairment, and depression (35,39,42,43). In addition, an increased risk of mortality in the 12 months after a severe hypoglycemic event in a large community-dwelling population was recently reported (44). These outcomes affect the cost of care as well as patient quality of life and activities of daily living.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular concern is the link between recurrent hypoglycemic events and cardiovascular risk, cognitive impairment, and depression (35,39,42,43). In addition, an increased risk of mortality in the 12 months after a severe hypoglycemic event in a large community-dwelling population was recently reported (44). These outcomes affect the cost of care as well as patient quality of life and activities of daily living.…”
Section: Discussionmentioning
confidence: 99%
“…These selfreported recurring SH patients had significantly more severe hypoglycaemia clinically and biochemically, and were more likely to be insulin treated. As well as self -reported antecedent SH in the previous month, 36.4 % of the calls in this pathway were made by people who made multiple calls to ambulance crew, with a small minority generating a large number of calls (> 3 each) accounting for nearly 18% of all calls, In other SH populations 31% [3], 37 % [11], or 12.7 % [18] of emergency SH ambulance contacts have been generated by repeat calls from the same patient(s), often relatively soon after the initial call, and up to 11% of patients have a further episode within 14 days [27]. These data suggest that while UK Ambulance Crew 'see and treat' policies are highly effective at treating individual SH events, and at keeping patients at home following SH treatment, they are treating and identifying a population with very high rates of recurrent SH events and repeat contact with emergency services.…”
Section: Discussionmentioning
confidence: 99%
“…This is important, as simple modelling based on ambulance call out rates in the UK and the prevalence of SH calls, suggests there are between 48,400 and 98,736 SH Ambulance call outs per annum [15,27] in the UK, and the scale of this activity has been apparent for some time (15). If we assume that perhaps one -third of these calls are from repeat callers [3,11], then there are perhaps up to 33,000 Ambulance SH calls per annum generated by repeat callers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have since demonstrated close associations between hypoglycemia, increased rate of cardiovascular disease, and mortality in T2DM patients [7][8][9][10][11][12][13] and possibly T1DM [10,14], further emphasizing the limitations of HbA1c as the sole measure of glycemic control.…”
Section: Introductionmentioning
confidence: 99%